RANCANG BANGUN PROTOTIPE ALAT PENGHITUNG PRODUK SECARA OTOMATIS DENGAN KONSEP INTERNET OF THING (IOT) BERBASIS MIKROKONTROLLER (ARDUINO UNO) - Sepriandi Parningotan; Tri Mulyanto (Electro Luceat, 2020)
The development of technology has changed the industry, especially manufacturing, into an industry that must be able to develop and compete globally through the convergence of information technology. The industrial sector requires innovation, especially in the aspect of mastery of technology which is a key determinant of competitiveness in the Industrial 4.0 era. IoT is a mutually integrated tool and can be used in the Industrial Age 4.0. Based on the problems that occur, it is necessary to conduct research and make a tool as a technology development in the internet-based warehouse management system of things using a microcontroller. With this tool system the activity of receiving and sending goods can be detected in quantity and product data automatically entered into the database quickly and precisely and allows one device to talk with other devices so that the recording, tracking, and movement of goods can be done in an integrated manner. The conclusion from this writing is that this tool will automatically count the products and enter or remove the product by scanning the QR code. Based on the test results, QRCode Scanner was successfully scanned with a maximum distance of 25 cm. The sensor can detect objects as far as 60 cm. In very bright lighting, bright and dim QR code scanning process is successfully carried out by the scanner. In the range of distance the Bluetooth connection can be fully controlled with a maximum distance of 160 cm.